Tensions and Problems of January 13 Narratives: From Legal Revenge to the Realization of Freedom - Černevičiūtė, Sigita; Zaksaitė, Salomėja (Lietuvos istorijos studijos, 2025)
he events of 13 January 1991 and the two criminal cases that resulted from them are, on the one hand, widely covered by the national media; however, on the other hand, there is a serious lack of an analytical approach (combining different perspectives) to the events, the cases, and the problems in general. Being a sensitive, mass-sensationalized topic is deceptive: it seems to be widely discussed, yet expert knowledge is lacking. It is noteworthy that the portrayal of the January 13th case and events is characterized by the patriotic discourse of basketball fans: if foreigners (in this case, communists) are playing, one should shout, trample, and scream – one should do everything to make ‘them’ appear unattractive – because then our own (i.e., the patriots who defended the freedom of the homeland) will, by default, seem admirable. Accordingly, the civic perception becomes black-and-white, one-sided, and superficial. This article is one of the few attempts to contextualize the issues discussed and to provide an argumentative approach to the matters at stake. The article consists of five parts: the first section explores the concept of political crime; the second presents the intersections and connections between law and criminology; the third discusses two opposing narratives of the events of January 13 and the issue of concept management; the fourth examines the expression of propagandistic imagery; and the fifth part reviews how victimological aspects of the January 13 events are reflected in the public discourse.